A wafer-level three-step calibration technique for BJT-based CMOS temperature sensor. (January 2023) - Gao, Ying; Liu, Xin; Jiang, Yanfeng
Abstract: In order to ensure the consistency of the fabricated devices in batches, calibration is required on CMOS temperature sensor before delivery to compensate the tracking errors of the devices. In the paper, a wafer-level three-step calibration technique for BJT-based CMOS temperature sensor is proposed and fabricated based on TSMC 180-nm-BCD technology. The calibration approach is based on the wafer level, with the simplified calibration process. The strategy of the fuse burning directly maps with the proposed three-step calibration approach. The technique shows encouraging results in removing the error band of the sensor response caused by processing variations in batch fabrication. The calibrated sensor can realize an inaccuracy (±3δ) within ±0.3 °C from −40 °C to 125 °C. The temperature sensor with the calibration module in the paper has great potential application in mobile phones, battery management, disk drives and other fields, etc. . Highlights: The technique can effectively reduce the error caused by process variations. The strategy of the fuse burning directly maps with the calibration approach. The chip is calibrated during the wafer level test based on probe station. The technique can realize an inaccuracy (±3δ) within ±0.3 °C from −40 °C to 125 °C.